2007
DOI: 10.1002/jsfa.3007
|View full text |Cite
|
Sign up to set email alerts
|

Safety tests and antinutrient analyses of noni (Morinda citrifolia L.) leaf

Abstract: The apparent lack of toxicity of the leaves and the hardiness of the plant make it ideal for further agricultural development, especially where sustained growth of other food crops is difficult. Copyright © 2007 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 23 publications
(21 reference statements)
2
28
0
1
Order By: Relevance
“…The leaves are also the source of a variety of other health-promoting commercial products available in Japan and the US, mainly for used to make infusions. Some manufacturers also produce capsules containing powdered noni leaves 16 . Previous studies revealed that noni leaves contain a variety of phytochemical constituents, including terpenoid, phytosterol, iridoid, flavonol, and anthraquinone compounds and their glycoside derivatives [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…The leaves are also the source of a variety of other health-promoting commercial products available in Japan and the US, mainly for used to make infusions. Some manufacturers also produce capsules containing powdered noni leaves 16 . Previous studies revealed that noni leaves contain a variety of phytochemical constituents, including terpenoid, phytosterol, iridoid, flavonol, and anthraquinone compounds and their glycoside derivatives [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…The results of their human clinical safety study using liver function measurements as well as subacute and subchronic animal toxicity tests showed no adverse effect on liver. West et al (2007) found no evidence of toxicity in the noni leaves which are also consumed by humans as food. Toxicological (genotoxicity tests) and analytical investigation (chemical analysis for anthraquinones) of the noni fruit juice revealed no genotoxic potential for human consumption, as genotoxic anthraquinones were not detected in the noni juice (Westendorf et al 2007).…”
Section: Safety Of Noni Fruitmentioning
confidence: 90%
“…Table 3. Ranges of amino acids in dried and roasted M. citrifolia leaves Data on the variability among French Polynesian M. citrifolia leaves have been provided for some phytochemicals, such as sterols, tannic acid, oxalic acid and tocopherols (West et al, 2007).…”
Section: Specification Of the Novel Food (Nf)mentioning
confidence: 99%